King USB2000 transmission.xlsx - Peter Hadden; Misha Vorobyev; William Hadden; Charles McGhee; Jie Zhang (2023)
These are the raw data obtained using a USB2000+ (Ocean Optics, Dunedin, Florida, USA) to determine the amount of light at each given wavelength transmitted through various ocular structures (cornea and lens) and through the whole eye of king penguins Aptenodytes patagonicus this is compared to the light recorded with no structure in place and from both is subtracted the light recorded with no actual light on. There is both the raw transmission data and the amount transmitted compared with the amount transmitted at 700 nm (SpectraMax), expressed as a decimel where the average transmission between 650 and 750 nm is 1.